Greater Adherence to the Portfolio Diet Is Associated with Lower Incidence of Type 2 Diabetes in the Women's Health Initiative. (7th June 2021) - Glenn, Andrea; Lo, Kenneth; Jenkins, David; Boucher, Beatrice; Hanley, Anthony; Kendall, Cyril; Shadyab, Aladdin; Tinker, Lesley; Chessler, Steven; Howard, Barbara; Liu, Simin; Sievenpiper, John
Abstract: Objectives: To assess the association of the plant-based cholesterol-lowering diet, the Portfolio Diet, with incident type 2 diabetes in women. Methods: We followed 147, 732 postmenopausal women initially free of diabetes in the Women's Health Initiative (WHI) Clinical Trials and Observational Study from 1993 through 2017. Adherence to the Portfolio Diet was assessed using an a priori diet index based on six food categories (high in plant protein [soy & pulses], nuts, viscous fiber, plant sterols and monounsaturated fat, and low in saturated fat) that were previously found to lower cardiovascular risk factors in the Portfolio Diet trials. We used Cox proportional-hazard models to estimate hazard ratios (HRs) and 95% confidence intervals (CI) of the association of adherence to a Portfolio Diet score with incident type 2 diabetes, adjusting for potential confounders (demographics, lifestyle behaviors, and medical history). The Portfolio Diet score was cumulatively assessed at baseline and year three using a validated food frequency questionnaire. Type 2 diabetes diagnosis was ascertained by self-reported medication use. Results: There were 14, 096 cases of incident type 2 diabetes over a mean follow-up of 14.3 years. In the fully adjusted models, adherence to the Portfolio Diet score was associated with a lower risk of incident type 2 diabetes (HR, 0.88, CIs, 0.83, 0.93; P for trend < 0.001), comparing the highest to lowest quartiles of adherence. Results remained similar across subgroup analyses (age, body mass index, family history of diabetes, and ethnicity) and several sensitivity analyses. Conclusions: Among postmenopausal women, higher adherence to the Portfolio Diet was associated with lower incident type 2 diabetes. These findings are the first to show that the Portfolio Diet may be associated with a lower risk of type 2 diabetes and warrants further investigation. Funding Sources: The WHI was funded by the National Heart, Lung, and Blood Institute, National Institutes of Health, and the U.S. Department of Health and Human Services. AJG was supported by the Banting & Best Diabetes Centre Tamarack Graduate Award in Diabetes Research, the Peterborough K.M. Hunter Charitable Foundation Graduate Award, and an Ontario Graduate Scholarship. JLS was funded by a Diabetes Canada Clinician Scientist Award.